Análisis de comportamiento caótico en variables de la cadena de suministro - Ramírez, Sergio A. (2011)
In this article we develop a supply chain model of four levels through the utilization of system dynamics with Ithink® and Mathlab® softwares to analyze data. The supply chain is studied from the chaos theory perspective, which helps identifying the sensitive variables that can lead to a state of chaos. A generic structure model that comprehends factory links, distribution, wholesale, retail and the client is constructed. The difficulty of operations and logistics managers to decide how much to order and when to do it is simulated accordingly to what occurs in the links of the preceding and subsequent levels with two decision parameters: The first parameter denominated A indicates the participation (between 0 and 1) of the number of product units that are taken into account in the actual stock and the pending orders at the moment of performing an order. The second parameter, denominated B, is the participation (between 0 and 1) of the number of units in the supply line (in transit) at the moment of performing orders of each of the links of the supply chain.